2013
DOI: 10.1103/physrevb.88.024105
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature structural effects in the (TMTSF)2PF6and AsF6Bechgaard salts

Abstract: We present a detailed low-temperature investigation of the statics and dynamics of the anions and methyl groups in the organic conductors (TMTSF) 2 PF 6 and (TMTSF) 2 AsF 6 (TMTSF: tetramethyl-tetraselenafulvalene). The 4 K neutron-scattering structure refinement of the fully deuterated (TMTSF) 2 PF 6 -D12 salt allows locating precisely the methyl groups at 4 K. This structure is compared to the one of the fully hydrogenated (TMTSF) 2 PF 6 -H12 salt previously determined at the same temperature. Surprisingly, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 50 publications
3
24
0
Order By: Relevance
“…This implies that the in-plane expansivities are dominated by anharmonic motions of the EtMe 3 P counterions. A dominant contribution of these isolated, weakly bound molecular units is consistent with recent results obtained on the metallic (TMTSF) 2 PF 6 salt [11]. There it was found that the thermal expansion coefficient is dominated by librational motions of the PF 6 units [11] which could be well described by Einstein oscillators.…”
Section: Resultssupporting
confidence: 89%
“…This implies that the in-plane expansivities are dominated by anharmonic motions of the EtMe 3 P counterions. A dominant contribution of these isolated, weakly bound molecular units is consistent with recent results obtained on the metallic (TMTSF) 2 PF 6 salt [11]. There it was found that the thermal expansion coefficient is dominated by librational motions of the PF 6 units [11] which could be well described by Einstein oscillators.…”
Section: Resultssupporting
confidence: 89%
“…This observation is complemented by a recent study 48 of the thermal dependence of the lattice expansivity of (TMTSF) 2 PF 6 below 200 K, which exhibits also high temperature negative contributions 99 , and whose analysis shows that anion rotation exhibits a huge Grüneisen parameter of Γ(PF 6 ) ≈ 28. A similar value of Γ(PF 6 ) is expected in (TMTTF) 2 PF 6 because the thermal expansion coefficients have the same magnitude in (TMTSF) 2 PF 6 and (TMTTF) 2 PF 6 .…”
Section: Anomalous Lattice Properties Of the Fabre Salts In Relamentioning
confidence: 62%
“…For example, in (TMTSF) 2 ReO 4 and BF 4 the AO transition drives a MI transition stabilizing a 2k F BCDW ground state. In (TMTSF) 2 ClO 4 the kinetics of AO drives the salt to either a SDW ground state (quenched samples) or a superconducting ground state (relaxed samples), for more details see 13,27,48 .…”
Section: Non Centro-symmetric Anionsmentioning
confidence: 99%
“…More precisely, the thermal variation of the lattice expansion in the direction i divided by T, α i /T, or more likely the volume expansion divided by T, (Σ i α i )/T, is proportional to the entropy derivative ∂S/∂T [34]. α ┴ /T taken from the data of [24] exhibits broad maxima around 30-40 K in (TMTSF) 2 PF 6 before dropping to zero at lower temperature [34]. This finding implies that below these maxima a net decrease of the "lattice" entropy, probably due to the vanishing of the structural disorder, should occur.…”
Section: Dimerization Of the Stackmentioning
confidence: 99%